Pengaruh Ekonomi Digital Platform Digital dan Pemasaran Digital Terhadap Tingkat Pendapatan UMKM Go Online di Kota Kediri - Tri Mianto Dion Prasetiyo; Sugeng Hadi Utomo (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
In the digital era provides a great opportunity for entrepreneurs especially a MSMEs to be developed their business because they get many conveniences and benefits as a result of the impact the digital era. This research was conducted to determine the impact of digital economic, digital platform and digital marketing to increasing Go Online MSMEs Revenue in Kediri. The number of respondents in this research were 60 persons, they are Go Online MSMEs owners which located in Kediri. This is quantitative research using primary data collected directly from participants through a questionnaire method. Additionally, the data analysis technique used in this is research multiple linear regression test. The results of this study suggest that if digital economic, platform digital, digital marketing separately give an impact to increasing Go Online MSME revenue in Kediri. Moreover, digital economic, platform digital, digital marketing overall impact increasing Go Online MSMEs revenue in Kediri.